Physical activity, physical condition and cardio-metabolic risk factors in young adults aged 18 to 29 - Suazo Fernández, Ricardo (2017)
Introduction: Physical activity and physical condition are determinants of cardio-metabolic risk factors, and may influence the incidence of chronic non-communicable diseases. Objectives: To analyze the association between physical activity level, physical condition and cardio-metabolic risk factors in young adults. Design: Observational, analytical and transversal study. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Graduate students from professional academic schools. Interventions: The sample was non-probabilistic, selected by convenience, it was formed by 149 men and women who voluntarily consented to participate. Those with cardiac, metabolic or physical disability which prevented the evaluation were excluded. Main outcome measures: Physical activity level (PAL), physical condition, cardio-metabolic risk factors. Results: 48.2% of the participants had high PAL. 53.7% had one or two altered cardio-metabolic risk factors: low HDL-cholesterol (43%), hypertension (8,7%), hyperglycemia (4%), hypertriglyceridemia (2.7%). 40.9% of women and 35.6% of men achieved optimal results in the evaluation of cardio-respiratory resistance. 49% of males and 34.9% of females obtained optimal results in abdominal strength assessment. 94.6% and 53.7% of participants achieved regular or deficient results in strength assessments of lower and upper limbs, respectively. Conclusions: In the subjects studied, high physical activity level was associated with the male sex, arterial hypertension, hypertriglyceridemia, overweight / obesity, and optimal results of cardio-respiratory resistance and abdominal muscle strength tests.